PERBANDINGAN UJI AKTIVITAS ANTI DIABETES EKSTRAK ETANOL BUAH PARE (Momordicacharantia L.) DAN DAUN LIDAH BUAYA (Aloe vera L.) PADA MENCIT JANTAN - Sitompul, Erly; Supartiningsih, Supartiningsih; Harefa, Karnerius; Sari, Samsia Yolanda (Jurnal Farmanesia, 2018)
Diabetes is a non-communicable degenerative disease that will increase in number in the future. This is evidenced by the increasing incidence of diabetes every decade. Bitter gourd and aloe vera are an alternative in treating Diabetes Mellitus because these plants contain saponins, flavonoids, and polyphenols (strong antioxidants), as well as glycosides cucurbitacin, momordicin, and charantin that can lower blood sugar, saponins, flavonoids, and alkaloids. This study aims to determine secondary metabolite compounds, anti-diabetic activity, and the combination of aloe vera extract and bitter melon extract that has antidiabetic activity. The method used in this study is an experimental method, namely testing the antidiabetic effect of extracts obtained from ethanol of bitter melon and aloe vera leaves on alloxan-induced mice. The results obtained from the research are that the administration of aloe vera extract 150 mg/kg BW and 200 mg/Kg BW, the group with the ethanol extract of bitter melon 150 mg/kg BW and 200 mg/Kg BW showed a very good effect on reducing BGD. This means that aloe vera extract 150 mg/kg BW and 200 mg/Kg BW, the group given ethanol extract of bitter melon 150 mg/kg BW and 200 mg/Kg BW had good antidiabetic activity.